Multiple views, sobering outcomes: a systematic review on the participation of children with disabilities in early childhood education and care - Dott, Janina; Licandro, Ulla (Frontiers in Education, 2025)
The participation of children with disabilities in early childhood education and care (ECEC) is not only a fundamental right, but also important for their development and well-being. However, the conceptualization of participation and the individual experiences of children in inclusive ECEC remain insufficiently understood. This systematic review aimed to investigate (1) how participation is defined and operationalized in empirical research and (2) the extent to which children with disabilities participate in inclusive ECEC. A search of peer-reviewed articles identified 28 relevant studies, which were analyzed using a narrative synthesis approach. Although the studies referenced similar conceptual frameworks, they used varied definitions of participation and related constructs. Most studies operationalized participation in terms of levels of involvement or engagement, assessed through observation tools or questionnaires. Findings suggest that children with disabilities participate less in ECEC activities and peer interactions than their peers without disabilities, with first indications to important influencing factors. The review underscores the need for further research into underlying mechanisms and the development of effective interventions.